Evaluation Of Different Fungicides Against Colletotrichum Truncatum Causing Anthracnose Of Soybean (Journal of Plant Disease Sciences, 2018)
Six systemic, four non systemic and four combi fungicides were evaluated at three concentrations in the laboratory for their efficacy against C. truncatum by poisoned food technique. The results revealed that all the fungicides, tested were found effective and significantly inhibited mycelial growth of the test pathogen over untreated control. Among the non systemic fungicides, mancozeb 75 WP recorded the highest mean inhibition (100 %) of mycelial growth of the test pathogen, followed by copper oxychloride 50 WP (93.58 %). Among the systemic fungicides the mean maximum per cent mycelial inhibition was recorded in difenconazole 25 EC (96.54 %), followed by propiconazole (92.77 %). Among the combi-fungicides, the mean maximum per cent mycelial inhibition was recorded in treatment with difenonazole 25 % + propiconazole 25 % EC (97.04 %), followed by carbendazim 25 % + mancozeb 50 % WS (92.96 %) and trifloxystrobin 25 % + tebuconazole 50 % WG (91.54 %).
Keywords: Soybean; Colletotrichum truncatum; fungicide inhibition